Micro-level determinants of lecture attendance and additional study-hours - Martin Ryan; Liam Delaney; Colm Harmon (University College Dublin, UCD School of Economics, 2010)
This paper uses novel measures of individual differences that produce new insights about student inputs into the (higher) education production function. The inputs examined are lecture attendance and additional study-hours. The data were collected through a web-survey that the authors designed. The analysis includes the following measures: willingness to take risks, consideration of future consequences and non-cognitive ability traits. Besides age, gender and year of study, the main determinants of lecture attendance and additional study-hours are attitude to risk, future-orientation and conscientiousness. In addition, future-orientation, and in particular conscientiousness, determine lecture attendance to a greater extent than they determine additional study. Finally, we show that family income and financial transfers (from both parents and the state) do not determine any educational input. This study suggests that non-cognitive abilities may be more important than financial constraints in the determination of inputs related to educational production functions.
hdl:10197/2658
Keywords: I21; J2; D90; 330; Higher education; Education inputs; Lecture attendance; Hours of study; Future-orientation; Attitude to risk; Non-cognitive ability; Conscientiousness